Facilitating Effects of Nanoparticles/Materials on Sensitive Immune-Related Lung Disorders. (20th July 2010) - Inoue, Ken-ichiro; Takano, Hirohisa
Abstract : Although the adverse health effects of nanoparticles/materials have been proposed and are being clarified, their facilitating effects on preexisting pathological conditions have not been fully examined. In this paper, we provide insights into the immunotoxicity of nanoparticles/materials as an aggravating factor in hypersusceptible subjects, especially those with immune-related respiratory disorders using our in vivo experimental model. We first exhibit the effects of nanoparticles/materials on lung inflammation induced by bacterial endotoxin (lipopolysaccharide: LPS) in vivo as a disease model in innate immunity, and demonstrated that nanoparticles instilled through both an intratracheal tube and an inhalation system can exacerbate the lung inflammation. Secondly, we introduce the effects of nanoparticles/materials on allergic asthma in vivo as a disease model in adaptive immunity, and showed that repetitive pulmonary exposure to nanoparticles has aggravating effects on allergic airway inflammation, including adjuvant effects on Th2-milieu. Taken together, nanoparticle exposure may synergistically facilitate pathological inflammatory conditions in the lung via both innate and adaptive immunological abnormalities.